Musik Seruling Bambu pada Kelompok Saiyo Sakato Desa Tebat Ijuk Kecamatan Depati VII “Deskripsi Musikologis” - Sepira, Qorie; Wimbrayardi Wimbrayardi; Ayuthia Mayang Sari (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study aims to examine the relationship between text and melody in Bamboo Flute Music in Depati VII District. This research is qualitative with a descriptive content analysis approach. The research object is Bamboo Flute Music, with data collected through literature study, observation, interviews, and documentation. The research analyzed the data by examining the form, melody, and the relationship between text and melody in the song